(2x+6)(3x-9)

()*()<--- Enter 2 Binomials Note: For multiple variable expressions, use our Expand Calculator

Multiply the 2 binomials: (2x + 6)(3x - 9)

The formula for this using the F-O-I-L (First-Outside-Inside-Last) method is:
(a + b)(c + d) = (a * c) + (b * c) + (a * d) + (b * d) where:
a = 2x, b = 6, c = 3x, and d = -9

Now plug these values into our formula and evaluate:
(2x + 6)(3x - 9) = (2x * 3x) + (6 * 3x) + (2x * -9) + (6 * -9)
(2x + 6)(3x - 9) = 6x2 + 18 - 18x - 54
(2x + 6)(3x - 9) = 6x2 - 54

Binomial 1 Times Binomial 2, that's the way we multiply through.